111k views
1 vote
What is the answer to this equation:
-18 = 9 + 6(y - 4)

User Adin
by
5.2k points

2 Answers

3 votes

Answer:


\large\boxed{y=-(1)/(2)=0.5}

Explanation:


-18=9+6(y-4)\qquad\text{use the distributive property}\\\\-18=9+6y+(6)(-4)\\\\-18=9+6y-24\qquad\text{combine like terms}\\\\-18=6y+(9-24)\\\\-18=6y-15\qquad\text{add 15 to both sides}\\\\-3=6y\qquad\text{divide both sides by 6}\\\\(-3)/(6)=(6y)/(6)\\\\-(3:3)/(6:3)=y\to y=-(1)/(2)

User OjamaYellow
by
5.0k points
7 votes

Answer: -3/6 (reduced is -1/2)

Explanation:

distribute the 6

-18 = 9 + 6y - 24

combine like terms on one side

-18 = -15 + 6y

get all like terms on one side

-3 = 6y

divide by 6

-3/6 = y

if you need to simplify or reduce the answer is -1/2.

User Dan Kuida
by
4.6k points